Semiautomated and Automated Quantitative Analysis of Corneal Sub-Basal Nerves in Patients With DED With Ocular Pain Using IVCM - Zhang, Yu; Wu, Yaying; Li, Wenbo; Huang, Xiaodan (Frontiers in Medicine, 2022)
Purpose Investigate the correlation and agreement between the results of semiautomated and fully automated quantitative analysis of the corneal sub-basal nerve plexus (SNP) in patients with dry eye disease (DED) with ocular pain using in vivo confocal microscopy (IVCM). Method A total of 50 voluntary participants were enrolled in this study, i.e., 25 DED patients with ocular pain and 25 healthy controls. Each patient underwent an evaluation of ocular symptoms that utilized: the Ocular Surface Disease Index (OSDI), the Ocular Pain Assessment Survey (OPAS), the tear film breakup time (TBUT) test, the Schirmer test, corneal staining, and IVCM. Five SNP images of the cornea of each eye were selected and analyzed using a semiautomated analysis software (NeuronJ) and a fully automated method (ACCMetrics) to quantify corneal nerve fiber density (CNFD), corneal nerve branch density (CNBD), and corneal nerve fiber length (CNFL). Results The intraclass correlation coefficient (ICC) of the CNFD (0.460 [0.382–0.532], p < 0.001), CNBD (0.608 [0.545–0.665], p < 0.001), and CNFL (0.851 [0.822–0.875], p < 0.001) represents the repeatability and consistency of measurements by the NeuronJ and ACCMetrics software. The CNFL values (r = 0.881, p < 0.001) obtained using the two methods have extremely high correlation, and similarly, the CNFD values (r = 0.669, p < 0.001) and CNBD values (r = 0.703, p < 0.001) are highly correlated. The CNFL had the biggest area under the curve (AUC; 0.747 [0.700–0.793], p < 0.001) when using ACCMetrics. In DED patients with ocular pain, the mean CNFD values for semiautomated and fully automated quantization were 23.5 ± 8.1 and 23.8 ± 8.6 n/mm2; the mean CNBD values were 46.0 ± 21.3, 35.7 ± 23.3 n/mm2; and the mean CNFL values were 19.3 ± 4.3 and 15.2 ± 3.8 mm/mm2, which were significantly lower than healthy subjects (p < 0.001). Conclusion There is a significant correlation between the measurements obtained via ACCMetrics and NeuronJ, especially for CNFL, which can be considered as the primary indicator in the diagnosis of DED with ocular pain. The SNP of the disease was significantly lower than that of healthy subjects.